Experience with direct molecular diagnosis of fragile X. - Mulley, J C (1992)
The utility of the pfxa3 probe for direct molecular diagnosis of the fragile X (FRAXA) has been established. This probe detects amplification of an unstable DNA element consisting of variable length CCG repeats. The size of the amplified fragment is correlated with phenotype and was determined using PstI digested DNA in family members. In 35 families with the fragile X, there was correspondence in 183 cases between the presence of an amplified unstable element and the presence of the fragile X chromosome independently determined by cytogenetics, position in the pedigree, or linked DNA markers flanking the fragile X. There was also correspondence in 124 cases between the presence of the normal 1.0 kb PstI fragment and absence of the fragile X chromosome independently determined by linked flanking markers. Six additional families considered to be isolated cases of 'fragile X' had been diagnosed before recognition of FRAXD. The pfxa3 probe confirmed the cytogenetic diagnosis in three families, the other three being rediagnosed as non-fragile X. A further two families had consistent expression of a different folate sensitive fragile site, FRAXE, close to FRAXA but not associated with fragile X syndrome and not detectable with the pfxa3 probe. Subsequent referrals were received from additional family members or from members of new families for whom carrier status had not been predetermined by linked markers. Direct pfxa3 diagnosis for the 135 females within these 222 additional cases was confirmed by dosage analysis with the control probe pS8.(ABSTRACT TRUNCATED AT 250 WORDS)